2022
DOI: 10.1007/s00167-022-06895-7
|View full text |Cite|
|
Sign up to set email alerts
|

The ALR-RSI score is a valid and reproducible scale to assess psychological readiness before returning to sport after modified Broström-Gould procedure

Abstract: Purpose Psychological readiness scores have been developed to optimize the return to play in many sports-related injuries. The purpose of this study was to statistically validate the ankle ligament reconstruction-return to sport injury (ALR-RSI) scale after modified Broström-Gould (MBG) procedure. Methods A similar version of the ACL-RSI scale with 12 items was adapted to quantify the psychological readiness to RTS after MBG and to describe construct valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
(52 reference statements)
2
23
0
Order By: Relevance
“…These findings indicated that the ALR-RSI score is a valid instrument that can assist physicians in assessing the psychological factors that may influence recovery following surgical management of peroneal tendon pathology in an active and sporting population. The results from prior studies [19,26] employing ALR-RSI to assess ankle instability patients were in line with the outcomes of the present study regarding correlation with PROMs, validity, internal consistency, reliability and discriminant capacity. Notably, this is the first paper that evaluates ALR-RSI in peroneal tendon pathology population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings indicated that the ALR-RSI score is a valid instrument that can assist physicians in assessing the psychological factors that may influence recovery following surgical management of peroneal tendon pathology in an active and sporting population. The results from prior studies [19,26] employing ALR-RSI to assess ankle instability patients were in line with the outcomes of the present study regarding correlation with PROMs, validity, internal consistency, reliability and discriminant capacity. Notably, this is the first paper that evaluates ALR-RSI in peroneal tendon pathology population.…”
Section: Discussionsupporting
confidence: 90%
“…The ALR-RSI was derived from the ACL-RSI and validated for ankle ligament reconstruction [26] and then for the modified Broström-Gould procedure [19]. It includes 12 items that pertain to performance confidence, risk assessment and emotions.…”
Section: Alr-rsi Scorementioning
confidence: 99%
See 1 more Smart Citation
“…A highly significant difference was found between the subgroup of patients who successfully returned to sport and those who did not 3 years after ankle ligament reconstruction (68.8 vs. 45.0 respectively) (Sigonney et al, 2020). This scale is used increasingly frequently after surgery and was recently validated among individuals with CAI who underwent a modified Broström-Gould procedure (Pioger et al, 2022). Results showed higher scores (61.9) in patients who returned to sports compared to those who no longer practiced a sport (43.4) 2 years after repair.…”
Section: Ankle Ligament Reconstruction-return To Sport After Injurymentioning
confidence: 99%
“…As the first‐line operative treatment of CLAI, anatomic lateral ankle ligament stabilisation using the modified Broström‐Gould (MBG) procedure has been proven to be reliable to achieve favourable outcomes in CLAI cases [31]. However, the reconstruction using tendon or other grafts was recommended for those with obesity, high sports demands and general joint laxity, especially when the remnant tissue was poor [7, 23, 26].…”
Section: Introductionmentioning
confidence: 99%